Deporte alternativo: una mirada sociológica ejemplificada desde el tchoukball (2018)
Alternative sport: a sociological view exemplified by Tchoukball, is an academic research that seeks to locate the most important sociological aspects of alternative sports, taking Tchoukball as an example. As for the collection of information, two study populations are chosen. In the first group, the an interview was made. For the case of the second study group, the interview format was used for five relatives of the young people interviewed, who do not formally practice this sport. The results shown here are presented in categories of analysis (qualitative). Finally, the research carried out is supported by a review of authors, both national and international, and with this we try to propose an opinion approach based on the Colombian context.